Phase Defects in Self-Focusing of Ultrashort Pulses - Eisenberg, H. S.; Silberberg, Y. (Phys. Rev. Lett., 1999)
We report the numerical observation of edge-type phase defects which occur during the self-focusing of ultrashort pulses. We identified two distinct kinds of defects, formed at the temporal or spatial edges of the pulse. We show the effect of phase defect creation on the dynamics and the eventual arrest of the self-focusing process. Phase defects often lead to the inversion of the phase fronts curvature, transforming contracting pulses into expanding pulses.
Publisher: American Physical Society